Teaching graduate political methodology - Brown, Mitchell; Nordyke, Shane; Thies, Cameron G.; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2022)
"Providing expert advice from established scholars in the field of political science, this engaging companion book to Teaching Undergraduate Political Methodology imparts informative guidance on teaching research methods across the graduate curriculum. Written in a concise yet comprehensive style, it illustrates practical and conceptual advice, alongside more detailed chapters focussing on the different aspects of teaching political methodology. Each chapter draws on practised teaching methods covering the what, how and when for teaching political methodology with an in-depth look at systematic research methods. The book is split into four distinct sections for graduate research methods education: the approach, the foundations of research design, quantitative analysis and qualitative analysis. Chapters offer evidence-based advice grounded in the science of teaching and learning (SoTL) literature from experienced, award-winning and highly recognized instructors of political methodology. Teaching Graduate Political Methodology will be required reading for faculty wanting to establish excellent methods for challenging subjects within the fields of political science, public administration and public policies. It will also serve as a useful resource for instructors wishing to gain greater student engagement with their courses by utilising different methods"--
Contents: Introduction to teaching graduate political methodology / Mitchell Brown, Shane Nordyke, and Cameron G. Thies -- Part I: Approaching research methods in the graduate political science curriculum -- 1. Transitioning from consumers of knowledge to producers of knowledge: Teaching scope and methods to doctoral students / James C. Garand -- 2. Teaching an introductory graduate methods course / John Ishiyama -- 3. Place-based versus online instruction / Daniel Hawes -- 4. Selecting texts / Jon Parker -- 5. Teaching introductory applied statistics with r / Timothy M. Peterson -- Part II: Foundations of research design -- 6. Do as i say, not as i do: The need to incorporate ethics in political science research methods curricula / Christi Siver and Colin Hannigan -- 7. Abstract blitzing and beyond: Teaching political methodology / Victor Asal -- 8. Research design and establishing causality / Stacey Pollard and Adrian Wolfberg -- 9. How to think conceptually without really trying: Notes on the teaching of concept analysis / Zachary Elkins -- 10. Teaching field experiments / Christopher W. Larimer -- 11. Teaching graduate students about sampling / Theodore Arapis -- 12. Teaching bias and error in research designs / Andrew Niesiobedzki -- 13. Learning by doing: Re-positioning surveys from an abstract to a practical tool / Adriano Udani and David C. Kimball -- Part III: Quantitative methods instruction -- 14. Data basics for graduate students / Soren Jordan -- 15. Teaching ordinary least squares regression / Michelle L. Dion -- 16. Extending regression to binary (and more!) outcomes / Soren Jordan -- 17. Teaching time series analysis / Clayton Webb -- 18. Nonparametric data / Carie Steele and Stephen Meserve -- 19. Replication / Cameron G. Thies -- 20. How to teach social network analysis to social science students / Olga Chyzh -- 21. Building a foundation for data science researchers in political science / Robert Bond -- 22. Data visualization / Alexis Henshaw an
Includes bibliographical references and index.
Keywords: elektronické knihy; electronic books; Political science -- Methodology; Political science -- Study and teaching